2014
DOI: 10.1128/mbio.00942-13
|View full text |Cite
|
Sign up to set email alerts
|

Heteroresistance at the Single-Cell Level: Adapting to Antibiotic Stress through a Population-Based Strategy and Growth-Controlled Interphenotypic Coordination

Abstract: Heteroresistance refers to phenotypic heterogeneity of microbial clonal populations under antibiotic stress, and it has been thought to be an allocation of a subset of “resistant” cells for surviving in higher concentrations of antibiotic. The assumption fits the so-called bet-hedging strategy, where a bacterial population “hedges” its “bet” on different phenotypes to be selected by unpredicted environment stresses. To test this hypothesis, we constructed a heteroresistance model by introducing a blaCTX-M-14 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 42 publications
0
56
0
Order By: Relevance
“…Indeed, in the environment, diversification of fitness strategies through phenotypic heterogeneity is a common strategy used by microbial populations to thrive even in adverse conditions. In this way, diversity of fitness strategies allows a heterogeneous population to have a higher probability of survival in the face of environmental fluctuations [52,53]. Bacterial populations in the environment are far more efficient when they operate according to the division of labor strategy [54,55].…”
Section: Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the environment, diversification of fitness strategies through phenotypic heterogeneity is a common strategy used by microbial populations to thrive even in adverse conditions. In this way, diversity of fitness strategies allows a heterogeneous population to have a higher probability of survival in the face of environmental fluctuations [52,53]. Bacterial populations in the environment are far more efficient when they operate according to the division of labor strategy [54,55].…”
Section: Opinionmentioning
confidence: 99%
“…For example, phenotypic heterogeneity and microbial antibiotic resistance, a phenotype termed 'persistence', have been long interpreted as a consequence of stochasticity in gene expression [53]. More recently, new analyses have pointed out the role of metabolism in bacterial persistence [62].…”
mentioning
confidence: 99%
“…Full automation of the MSP method may be realized with commercially available motorized colony pickers, though these systems are currently very expensive. We believe that the MSP work flow could be used with various droplet-based microfluidic systems to facilitate many applications, such as studies of cellular heterogeneity (41), selection of mutants, and adherent-cell or microbial biofilm cultivation. In addition, the spiral droplet array generated by an automated dish drive is addressable, which facilitates serial dilution and dose-response screening.…”
Section: Discussionmentioning
confidence: 99%
“…Heteroresistance was followed on a single-cell level owing to the fusion with green fluorescent protein. This study showed that cells with hydrolase overexpression formed the majority of the population upon increasing antibiotic concentrations, due to decreased growth rates rather than selection for resistant cells (136).…”
Section: Heteroresistance To ␤-Lactamsmentioning
confidence: 99%
“…This permitted monitoring of heteroresistant bacteria, since a subset of the cells expressed more hydrolase and hence exhibited a higher level of resistance to ceftriaxone (136). Heteroresistance was followed on a single-cell level owing to the fusion with green fluorescent protein.…”
Section: Heteroresistance To ␤-Lactamsmentioning
confidence: 99%